2012
DOI: 10.3748/wjg.v18.i24.3138
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of total splenic artery embolization and partial splenic embolization for hypersplenism

Abstract: Our results indicate that TSAE for patients with hypersplenism not only delivers a better long-term outcome, but is also associated with lower complication rates and a shorter hospital stay than PSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 19 publications
2
21
0
3
Order By: Relevance
“…Hiroshi Yoshida et al [12] reported that PSE following obliteration of portal-systemic shunt reduces serum ammonia levels, and improves portal systemic encephalopathy, which might explain the result observed in our study that HE in group B did not worsen significantly, and was significantly lower than that of group A. Previous studies [6,19] demonstrated that WBC and PLT counts after PSE increased significantly than those before PSE. Consistent with these findings, patients receiving TIPS and PSE in our study had significantly increased WBC and PLT counts.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Hiroshi Yoshida et al [12] reported that PSE following obliteration of portal-systemic shunt reduces serum ammonia levels, and improves portal systemic encephalopathy, which might explain the result observed in our study that HE in group B did not worsen significantly, and was significantly lower than that of group A. Previous studies [6,19] demonstrated that WBC and PLT counts after PSE increased significantly than those before PSE. Consistent with these findings, patients receiving TIPS and PSE in our study had significantly increased WBC and PLT counts.…”
Section: Discussionsupporting
confidence: 74%
“…Risk factors for recurrent bleeding include an insufficient decrease in portosystemic pressure gradient after TIPS creation alone [4] . Partial splenic arterial embolization(PSE), which has been an established interventional approach for portal hypersplenism [5,6] , appears to be efficatious to in reducing episodes of variceal bleeding [7,8] , improving hematologic parameters [9,10] , enhancing hepatic protein synthesis [11] , and reducing severity of HE [12] .…”
Section: Introductionmentioning
confidence: 99%
“…On the Other hand; He et al. , performed PSE for 34 patients with hypersplenism and reported 100% technical success.…”
Section: Discussionmentioning
confidence: 99%
“…The potential complications include post-embolisation syndrome, splenic abscess, splenic rupture, refractory ascites, distal pancreatitis and gastrointenstinal bleeding 5 6. Pulmonary disorders, such as pneumonia, atelectasis and pleural effusions, are the other potential complications, which usually develop in the left lung and are associated with embolisation of the upper pole of the spleen 4.…”
Section: Discussionmentioning
confidence: 99%